2004
DOI: 10.1016/j.cplett.2003.12.126
|View full text |Cite
|
Sign up to set email alerts
|

Cold wall CVD generation of single-walled carbon nanotubes and in situ Raman scattering measurements of the growth stage

Abstract: Catalytic CVD generation of high-purity single-walled carbon nanotubes (SWNTs) without use of an electric furnace or a hot-filament is demonstrated. High-purity SWNTs were generated from alcohol used as a carbon source with Fe/Co particles supported on zeolite by Joule-heating of a silicon base plate. This technique was applied for an in situ measurement of Raman scattering during the growth stage in a vacuum chamber equipped with an SPM/Raman detector. The surface temperature was measured by a systematic shif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
63
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(64 citation statements)
references
References 33 publications
1
63
0
Order By: Relevance
“…To compare more directly with other in situ Raman studies, a roughly linearly increasing G band with time was observed by Chiashi et al [1]. However, the time resolution was lower, growth was halted before saturation was observed, and other bands were not visible in situ.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…To compare more directly with other in situ Raman studies, a roughly linearly increasing G band with time was observed by Chiashi et al [1]. However, the time resolution was lower, growth was halted before saturation was observed, and other bands were not visible in situ.…”
Section: Resultsmentioning
confidence: 92%
“…An early spectroscopic study reported a linear increase in the G band signal during CVD using a zeolite/Fe Co-based catalyst and ethanol vapor as the carbon source [1]. In a combined Raman spectroscopy global Raman imaging (GRI) study, we were able to detect SWNTs as they formed in the reactor and to trace out the D and G band evolution [2].…”
mentioning
confidence: 96%
“…In previous in situ Raman studies of CVD growth, Chiashi et al reported a linear increase in G band intensity during growth. 1 In subsequent work, we observed an exponential initial stage, as well as a gradual saturation stage for both D and G bands during low-temperature growth. 7 A similar shape for the Raman evolution can be discerned in data from laser heating CVD experiments.…”
Section: Introductionmentioning
confidence: 98%
“…Forests were grown in a cold-walled CVD reactor (which provides excellent optical access to the sample [27][28][29][30]) operated at atmospheric pressure as described previously [21], with additional details given in other references [27,28]. Forests were imaged in situ through a large glass window using a long focal length optical microscope and camera at an ∼5…”
Section: Methodsmentioning
confidence: 99%